An eco-friendly physicocultural-based rapid synthesis of selenium nanoparticles. Issue 54 (16th May 2016) - Shirsat, Shubhangi; Kadam, Ambadas; Jadhav, Vijaykumar V.; Zate, Manohar K.; Naushad, Mu.; Pawar, B. N.; Mane, Rajaram S.; Kim, Kwang Ho
Abstract : A rapid synthesis of stable and smaller sized Se NPs was achieved in tryptic soya medium maintained at pH ∼9, temperature ∼50 °C, and a 9 mM Se oxyion concentration. Abstract : The eco-friendly, safe, and cost-effective synthesis of selenium (Se) nanoparticles (NPs) by microorganisms is an important branch of nanotechnology and is considered to be a green synthesis. Functional biosynthesized Se NPs find various applications if they are have definite shapes and sizes, which can be obtained by controlling the cultural conditions and physical operation parameters during the biosynthesis process. We depict the rapid (∼12 h) synthesis of Se NPs using a tryptic soy broth culture under the experimental conditions of pH ∼9, temperature ∼50 °C, in sunlight. The optimized conditions helped us to synthesize chemically and environmentally stable Se NPs. The main aim of the present study is to optimize the different cultural media, temperature, pH, light intensity, concentration of selenium dioxide, and the time of reaction for the rapid blend of Se NPs by Pantoea agglomerans .